Academic pipeline or academic treadmill? Postdoctoral fellowships and the circular logic of "development" - Kerr, P. (South African Journal of Higher Education, 2022)
South African higher education policy related to postdoctoral fellowships is informed by two related discourses: the discourse of the “academic pipeline” and the discourse of “human capital development”. Both of these are forward-looking concepts which imply that good things lie in future employment for postdocs, and/or increased competitiveness and employment for the nation. This article, which is part autoethnography and part higher education policy analysis, offers a critique of these discourses by narrating the author’s own transition from postgraduate psychology student to contract worker, postdoctoral fellow, unsuccessful permanent job applicant, and finally to accepting an offer of a permanent academic job outside South Africa. While seeing myself as one of these early-career academics in the “pipeline” which the policy documents purport to address, I discuss how research managers use discourses of career development and human capital development to mislead young academics about their academic employment prospects and silence their attempts to critique the system. The article proposes that the concept of the academic pipeline works to obscure how postdoctoral fellowships are part of the casualisation and de-professionalisation of academic work, through which disciplinary identity and accomplishments are being divorced from secure university employment.